Effects of Estrogen Replacement on Bone Geometry and Microarchitecture in Adolescent and Young Adult Oligoamenorrheic Athletes: A Randomized Trial. (7th November 2019) - Ackerman, Kathryn E; Singhal, Vibha; Slattery, Meghan; Eddy, Kamryn T; Bouxsein, Mary L; Lee, Hang; Klibanski, Anne; Misra, Madhusmita
ABSTRACT: Oligoamenorrheic athletes (OAs) have lower bone mineral density (BMD) and greater impairment of bone microarchitecture, and therefore higher fracture rates compared to eumenorrheic athletes. Although improvements in areal BMD (aBMD; measured by dual‐energy X‐ray absorptiometry) in OAs have been demonstrated with transdermal estrogen treatment, effects of such treatment on bone microarchitecture are unknown. Here we explore effects of transdermal versus oral estrogen versus no estrogen on bone microarchitecture in OA. Seventy‐five OAs (ages 14 to 25 years) were randomized to (i) a 100‐μg 17β‐estradiol transdermal patch (PATCH) administered continuously with 200 mg cyclic oral micronized progesterone; (ii) a combined 30 μg ethinyl estradiol and 0.15 mg desogestrel pill (PILL); or (iii) no estrogen/progesterone (NONE) and were followed for 12 months. Calcium (≥1200 mg) and vitamin D (800 IU) supplements were provided to all. Bone microarchitecture was assessed using high‐resolution peripheral quantitative CT at the distal tibia and radius at baseline and 1 year. At baseline, randomization groups did not differ by age, body mass index, percent body fat, duration of amenorrhea, vitamin D levels, BMD, or bone microarchitecture measurements. After 1 year of treatment, at the distal tibia there were significantly greater increases in total and trabecular volumetric BMD (vBMD), cortical area and thickness, and trabecular number in the PATCH versus PILL groups. Trabecular area decreased significantly in the PATCH group versus the PILL and NONE groups. Less robust differences between groups were seen at the distal radius, where percent change in cortical area and thickness was significantly greater in the PATCH versus PILL and NONE groups, and changes in cortical vBMD were significantly greater in the PATCH versus PILL groups. In conclusion, in young OAs, bone structural parameters show greater improvement after 1 year of treatment with transdermal 17β‐estradiol versus ethinyl estradiol–containing pills, particularly at the tibia. © 2019 American Society for Bone and Mineral Research.